Rethinking Design Education: The Role of Universal Design in a Sustainable Future - Bruno Oro; Subinay Malhotra (DIID, 2024)
This paper explores the critical gap in integrating Universal Design (UD) into U.S. design education, where sustainability is often prioritized while inclusivity remains elective. Through an ongoing study of 60 universities, initial findings reveal that only two briefly mention UD, and none fully integrate it into their core design programmes. This highlights a disconnect between inclusive values and educational structures. UD, like sustainability, offers broad social and commercial benefits by reducing stigma, expanding markets, and fostering equity. By embedding UD into foundational courses, design education can better prepare students to address environmental and social challenges. This paper argues for UD’s structural inclusion, not as an add-on, but as a key framework for shaping equitable and sustainable futures in design.